(x^2-2xy+2y^2)(x^2+y^2)+2x^3y-3x^2y^2+2xy^3 Với x=-1/2,y=1/2 25/07/2021 Bởi Adalynn (x^2-2xy+2y^2)(x^2+y^2)+2x^3y-3x^2y^2+2xy^3 Với x=-1/2,y=1/2
`(x^2-2xy+2y^2)(x^2+y^2)+23^2y-3x^2y^2+2xy^3` `= x^4-2x^3y+2x^2y^2+x^2y^2-2xy^3+2y^4+2x^3y-3x^2y^2+2xy^3` `= x^4+2y^4` `= (-1/2)^4+2.(1/2)^4` `= 1/16+2. 1/16` `= 1/16.(1+2)` `= 1/16.3` `=3/16` Bình luận
`(x²-2xy+2y²)(x²+y²)+2x³y-3x²y²+2xy³` `= x^4-2x³y+2x²y²+x²y²-2xy³+2y^4+2x³y-3x²y²+2xy³` `= x^4+2y^4` `= (-1/2)^4+2.(1/2)^4` `= 1/16+2. 1/16` `= 1/16.(1+2)` `= 1/16 .3=3/16` Bình luận
`(x^2-2xy+2y^2)(x^2+y^2)+23^2y-3x^2y^2+2xy^3`
`= x^4-2x^3y+2x^2y^2+x^2y^2-2xy^3+2y^4+2x^3y-3x^2y^2+2xy^3`
`= x^4+2y^4`
`= (-1/2)^4+2.(1/2)^4`
`= 1/16+2. 1/16`
`= 1/16.(1+2)`
`= 1/16.3`
`=3/16`
`(x²-2xy+2y²)(x²+y²)+2x³y-3x²y²+2xy³`
`= x^4-2x³y+2x²y²+x²y²-2xy³+2y^4+2x³y-3x²y²+2xy³`
`= x^4+2y^4`
`= (-1/2)^4+2.(1/2)^4`
`= 1/16+2. 1/16`
`= 1/16.(1+2)`
`= 1/16 .3=3/16`